Puzzle: Waterfall Valley - Buffalo Puzzles (Buffalo, NY, 2020 Buffalo Games & Puzzles, Inc.)
Puzzle image shows a rural hillside containing a waterfall, a church, a granary, houses, a covered bridge, a railroad, and trees with bright autumn colors
Keywords: Americana Collection -- Jigsaw Puzzle; Autumn -- Jigsaw Puzzle; Fall foliage -- Jigsaw Puzzle